Cytotoxicity screening of 114 Mongolian plant extracts on liver, colon, breast, and cervix cancer cell lines - Oidovsambuu, Sarangerel; Tsagaantsooj, Tuul; Bekh-Ochir, Davaapurev; Myagmar, Nomin; Batjikh, Indra; Erdenebileg, Saruul; Munkhuu, Orgilkhatan; Oidovsambuu, Odgerel; Javzan, Batkhuu (Mongolian Journal of Chemistry, 2024)
A total of 114 Mongolian plant species were subjected to cytotoxicity screening against liver (HepG2), colon (HCT116), breast (MCF7), and cervical (HeLa) cancer cell lines. Among them, ethanolic extracts of Androsace incana, Artemisia rutifolia, Saussurea amara, and Inula salsoloides exhibited remarkable cytotoxicity, with IC50 values below 1.5 μg/mL against at least 2 tested cell lines when treated for 48 hours. Erysimum flavum, Juniperus sibirica, and Stellaria dichotoma demonstrated selective cytotoxicity against specific cancer cell lines. Extracts from 23 plant species, such as Artemisia xerophytica, Ajania trifida, Melandrium brachypetalum, Brachanthemum mongolicum, and Rhinanthus songaricus, showed moderate toxicity. Further research on the phytochemicals and biological activities of these species is crucial for a deeper understanding and potential applications. These screening results of the cytotoxic effects of numerous Mongolian plants could establish a foundational dataset for subsequent comprehensive studies on the screened plants.